Hyperkalemia in patients undergoing hemodialysis: Its pathophysiology and management. Issue 1 (31st August 2021) - Shibata, Shigeru; Uchida, Shunya
Abstract: Potassium is a major intracellular cation in the body, regulating membrane potential of excitable cells, such as cardiomyocytes and skeletal muscle cells. Because the kidney plays a critical role in controlling potassium balance, the elevation in serum potassium levels is one of the most common complications in patients with maintenance hemodialysis (MHD). In addition to reduced renal potassium excretion, the alteration in body potassium distribution owing to comorbid conditions may also contribute to dyskalemia. Besides potassium elimination through hemodialysis in MHD patients, accumulating data indicate the potential importance of extra‐renal elimination involving the gastrointestinal system, which can be affected by the inhibitors of the renin‐angiotensin‐aldosterone system. In this article, the literature on potassium physiology in MHD patients is reviewed with an emphasis on the changes from individuals with normal kidney function. This article also summarizes the findings of recent studies on dietary control, dialysate prescription, and pharmacological therapy.